The influence of biological maturity on dynamic force-time variables and vaulting performance in young female gymnasts - Moeskops, S.; Oliver, J. L.; Read, P. J.; Cronin, J. B.; Myer, G. D.; Haff, G. G.; Moore, I. S.; Lloyd, R. S. (Journal of Science in Sport and Exercise, 2020)
Purpose: This cross-sectional study investigated dynamic force-time variables and vaulting performance in young female gymnasts of different maturity status. Methods: 120 gymnasts aged 5-14 years were sub-divided into maturity groupings using percent of predicted adult height (%PAH) attained. Participants performed three jumping protocols, the squat jump (SJ), countermovement jump (CMJ) and drop jump (DJ), before completing straight jump vaults that were recorded using two-dimensional video. Results: Jumping performance improved with biological maturity evidenced by the most mature gymnasts` producing significantly more absolute force (P < 0.05; all d > 0.78), impulse (P < 0.05; all d > 0.75) and power (P < 0.05; all d > 0.91) than the least mature group, resulting in the greater jump heights (P < 0.05; all d > 0.70). While, no significant differences were observed in relative peak force across multiple tests, measures of relative peak power did significantly increase with maturity. Based upon regression analyses, maturation was found to influence vertical take-off velocity during vaulting, explaining 41% of the variance in each jumping protocol. Across all tests, the DJ was found to have the highest predictive ability of vaulting vertical take-off velocity, explaining 55% of the total variance. Conclusion: Biological maturation impacts jump height and underpinning mechanical variables in young female gymnasts. Vaulting vertical take-off velocity appears to be influenced by maturation and various dynamic force-time variables, particularly those during DJ, which had the highest explained total variance.